Happiness-Concept, Measurement and Promotion - Ng, Yew-Kwang (Springer Nature, 2022)
This open access book defines happiness intuitively and explores several common conceptual mistakes with regard to happiness. It then moves on to address topical issues including, but not limited to, whether money can buy you happiness, why happiness is ultimately the only thing of intrinsic value, and the various factors important for happiness. It also presents a more reliable and interpersonally comparable method for measuring happiness and discusses twelve factors, from A to L, that are crucial for individual happiness: attitude, balance, confidence, dignity, engagement, family/friends, gratitude, health, ideals, joyfulness, kindness and love. Further, it examines important public policy considerations, taking into account recent advances in economics, the environmental sciences, and happiness studies. Novel issues discussed include: an environmentally responsible happy nation index to supplement GDP, the East Asian happiness gap, a case for stimulating pleasure centres of the brain, and an argument for higher public spending.